Reformulasi Pemikiran Islam Tradisional: Studi Pemikiran Abdullah Saeed Tentang Fazlur Rahman - Apri Wardana Ritonga; Hasnil Oktavera; Ernawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore Abdullah Saeed's thoughts about Fazlur Rahman, namely Rahman’s critique of traditional Islam, Rahman's framework for interpretation, and an assessment of Rahman’s contribution. This study is a literature review using analytical descriptive methods with primary and secondary data sources from literature materials. The results of this study show that: first, Fazlur Rahman highlights that traditional Islam tends to be trapped in backwardness of thought due to stagnant interpretation and interpretation of sacred texts. He emphasized that thinkers and ulama should make serious efforts to adapt Islamic understanding to changing times and social dynamics; secondly, to understand the Qur’an correctly, we must understand the text in its historical context and relate it to universal values that can be applied in the context of modern times; and third, Abdullah Saeed appreciated Fazlur Rahman's great contribution to the world of contemporary Islamic thought. According to him, Fazlur Rahman opened a new path in the interpretation of the Qur’an with a more dynamic and progressive approach in the form of a method of interpreting the Qur’an that takes into account historical, social context, and universal values, allowing for a broader and more relevant understanding of how to convey the messages of the Koran in modern times.